Bringing Digital Learning to Madrasah Ibtidaiyah: Undestanding Its Influence on Student Motivation and Engagement in Grades 4-6 - Kharis Sulaiman Hasri; Wahyu Iskandar; Suwandi Simangunsong (Yayasan Zia Salsabila, 2025)
This research examines the influence of digital learning on student motivation and engagement in Madrasah Ibtidaiyah, particularly in grades 4-6. Despite the development of digital technology, the implementation of digital learning in madrasah is still limited and not optimal in influencing the learning process. The main issue raised is the extent to which digital technology can increase students' learning motivation and engagement in the madrasah environment. The purpose of this study is to understand the impact of digital learning on student motivation and engagement, as well as to identify factors that support or hinder its implementation. This research used a qualitative approach, with data collection through in-depth interviews and observation. Data was analyzed using N-Vivo assistance. The results show that digital learning significantly increases student motivation and engagement, with factors such as interactivity of digital media, use of relevant content, and teacher support playing an important role in the achievement. The main impact of this study is to provide insights for curriculum development and teacher training to improve the effectiveness of technology-based learning in madrasah.